Polyoxometalate-based layered nano-tubular arrays: facile fabrication and superior performance for catalysis1. Issue 31 (8th April 2015) - Zhen, Hongpeng; Li, Xiaolin; Zhang, Lijuan; Lei, Huan; Yu, Chao; Zhou, Yunshan; Hassan, Sadaf ul; Qin, Libo; Asif, Hafiz Muhammad
<x xml:space="preserve">Abstract</x> Keggin-type polyoxoanion PW12O403−-containing one-dimensional nano-tubular arrays fabricated within porous templates show a superior performance just through simple filtrating processes.